Spatially Resolved Transcriptomes—Next Generation Tools for Tissue Exploration - Asp, Michaela; Bergenstråhle, Joseph; Lundeberg, Joakim (BioEssays, 2020)
Recent advances in spatially resolved transcriptomics have greatly expanded the knowledge of complex multicellular biological systems. The field has quickly expanded in recent years, and several new technologies have been developed that all aim to combine gene expression data with spatial information. The vast array of methodologies displays fundamental differences in their approach to obtain this information, and thus, demonstrate method‐specific advantages and shortcomings. While the field is moving forward at a rapid pace, there are still multiple challenges presented to be addressed, including sensitivity, labor extensiveness, tissue‐type dependence, and limited capacity to obtain detailed single‐cell information. No single method can currently address all these key parameters. In this review, available spatial transcriptomics methods are described and their applications as well as their strengths and weaknesses are discussed. Future developments are explored and where the field is heading to is deliberated upon. In this review, current spatial transcriptomics methods are surveyed. These methods detect RNA molecules while retaining information of where the molecules are located in the tissue. The advantages and drawbacks of existing methods are discussed.